BIMBINGAN TEKNIS MANAJEMEN KEPALA SEKOLAH DAN PENGELOLAAN PEMBELAJARAN DI SMA RAPI MANADO - Mondolang, Aswin Hermanus (Jurnal Layanan Masyarakat (Journal of Public Services), 2020)
A very urgent problem in Manado's RAPI High School is the management of school principals specifically covering: setting vision and mission, goals, work programs, and implementing school programs, carrying out supervision and monitoring, and evaluating work programs. The management of learning by teachers includes: the preparation of learning plans, the implementation and assessment of learning, and carrying out classroom action research. Through community service activities with the provision of technical management guidance to school principals and management of learning to teachers, it is expected to increase the ability of school principals and teachers. The Principal is able to compile the vision and mission of the school, compile or formulate school goals, compile school work programs and develop work programs for school principals. The teachers have also demonstrated the ability to carry out learning evaluations and are able to prepare CAR proposals. Through this activity it can be concluded that the activity participants can improve their management abilities, and the ability to manage learning in RAPI Manado High Schools. Abstrak Permasalahan yang sangat urgen pada SMA Rapi Manado adalah manajemen kepala sekolah secara spesifik meliputi: penetapan visi dan misi, tujuan, program kerja, dan pelaksanaan program sekolah, melaksanakan supervisi dan monitoring, dan mengevaluasi program kerja. Pengelolaan pembelajaran oleh guru meliputi: penyusunan perencanaan pembelajaran, pelaksanaan dan penilaian pembelajaran, serta melaksanakan penelitian tindakan kelas. Melalui kegiatan pengabdian dengan metode pemberian bimbingan teknis manajemen kepada kepala sekolah maupun pengelolaan pembelajaran kepada para guru maka diharapkan peningkatan kemampuan Kepala Sekolah dan Guru. Kepala Sekolah mampu menyusun visi dan misi sekolah, menyusun /merumuskan tujuan sekolah, menyusun program kerja sekolah dan menyusun program kerja kepala sekolah. Para guru juga telah memperlihatkan kemampuan dalam melaksanakan evaluasi pembelajaran serta mampu menyusun proposal PTK. Melalui Kegiatan ini dapat disimpulkan bahwa para peserta kegiatan (Kepala Sekolah dan guru-guru SMA Rapi Manado) dapat meningkatkan kemampuan manajemennya, dan kemampuan mengelola pembelajaran di SMA Rapi Manado.